1977
DOI: 10.1121/1.381372
|View full text |Cite
|
Sign up to set email alerts
|

Difference thresholds for interaural intensity

Abstract: In an earlier paper, wqe examined the distribution of binaural resolvins power by measuring threshold increments of interaural delay as a function of overall dealy [E. R. Hafter and J. Demaio, J. Acoust. Soc. Am. 57, 181–187 (1975)]. In the current study, similar measures were made for interaural increments of intensity. As before, the stimuli were bandpass clicks of either low (0. 1–2 kHz) or hish (3–4 kHz) frequency. For overall interaural differences as sreat as 24 dB, it seems that performance was based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 13 publications
6
17
0
Order By: Relevance
“…Moreover, the best-threshold ILDs of most neurons occurred near the midline, for pedestal ILDs between ϩ5 and Ϫ5 of 0 dB. The low-threshold ILDs Ͻ1 dB near pedestals of 0 dB are consistent with psychophysical findings of best acuity for ILD (Hafter et al, 1977;Yost and Dye, 1988) and azimuth (Mills, 1958).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Moreover, the best-threshold ILDs of most neurons occurred near the midline, for pedestal ILDs between ϩ5 and Ϫ5 of 0 dB. The low-threshold ILDs Ͻ1 dB near pedestals of 0 dB are consistent with psychophysical findings of best acuity for ILD (Hafter et al, 1977;Yost and Dye, 1988) and azimuth (Mills, 1958).…”
Section: Discussionsupporting
confidence: 75%
“…Yost and Dye (1988) also report thresholds at midline (ILD, 0 dB) ranged from 0.6 to 1.2 dB (depending on frequency), which is comparable with the 0.9 dB (value of the lower envelope at 0 dB ILD) threshold ILD found here. Hafter et al (1977) found thresholds of ϳ1.5 dB at midline. Recall that low neural threshold ILDs were found across a broad range of neural CFs and, thus, stimulus frequencies (Fig.…”
Section: Ild Thresholds As Function Of Pedestal Ildmentioning
confidence: 99%
See 1 more Smart Citation
“…The work of Domnitz and Colburn (1977) confirmed earlier findings (Rowland and Tobias, 1967;Elfner and Perrott, 1967;Hershkowitz and Durlach, 1969;Yost, 1974;Hafter and DeMaio, 1975;Hafter et al, 1977) that showed that sensitivity to interaural differences was usually diminished when the lateral images were located away from midline by introducing an interaural difference of time or level.…”
Section: Introductionsupporting
confidence: 87%
“…By comparison, the ILD JNDs clearly increased with ILD magnitude (Fig. 3) and are comparable to those previously reported by Yost and Dye (1988) out to the maximum offset they tested (15 dB ILD) and slightly higher at lower offsets than those reported by Hafter et al (1977). Again, these changes in binaural sensitivity cannot by themselves explain the magnitude of the increases in MAA as a function of eccentricity which must then also reflect the spatial variation in the acoustic cues.…”
Section: Discussionsupporting
confidence: 66%